2018
DOI: 10.14411/eje.2018.035
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of insects associated with two common plants in the Brazilian Cerrado: Responses of two guilds of herbivores to bottom-up and top-down forces

Abstract: The Trophic Cascade Theory has been used to explain the organization of herbivorous insect communities in tropical ecosystems. In addition, the insect community associated with a species of plant can also be determined by the geographical distribution and taxonomic isolation of the plant. In this study, the following predictions about the number of herbivores associated with particular host plants were tested: (i) plant species belonging to large taxonomic groups with broad geographical distributions have a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 68 publications
(76 reference statements)
1
18
0
Order By: Relevance
“…Galling insect networks were less modular and more specialised than exophagous insect networks, and sucking insect networks were more specialised than chewing insect networks. These results corroborate previous studies, showing that endophagous and exophagous herbivores have different patterns of interactions with their host plants (Gaston et al ., ; Araújo ; Kuchenbecker & Fagundes, ). In addition, we also found that network connectance and specialisation depend on network size, as already described in previous studies (Dunne et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Galling insect networks were less modular and more specialised than exophagous insect networks, and sucking insect networks were more specialised than chewing insect networks. These results corroborate previous studies, showing that endophagous and exophagous herbivores have different patterns of interactions with their host plants (Gaston et al ., ; Araújo ; Kuchenbecker & Fagundes, ). In addition, we also found that network connectance and specialisation depend on network size, as already described in previous studies (Dunne et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that may have contributed to the modular structure in exophage networks is the large number of singleton species (Novotný & Basset, ). The occurrence of rare species is common in communities of tropical insect herbivores (Price et al ., ; Lewinsohn et al ., ; Novotný & Basset, ), including Neotropical savannas (Kuchenbecker & Fagundes, ), and may increase the modularity in plant–herbivore networks (Dormann & Strauss, ).…”
Section: Discussionmentioning
confidence: 99%
“…The structure of gall‐inducing insect communities can be determined by environmental factors (Blanche, ; Butterill & Novotny, ; Craig, Itami, & Craig, ; Cuevas‐Reyes, Quesada, & Oyama, ; da Costa, de Siqueira Neves, de Oliveira Silva, & Fagundes, ; Price, ), by top‐down (Fagundes, Neves, & Fernandes, ; Price, ) or bottom‐up (Egan & Ott, ; Espírito‐Santo, de S. Neves, Andrade‐Neto, & Fernandes, ; Hunter & Price, ; Malinga, Valtonen, Nyeko, Vesterinen, & Roininen, ) mechanisms, and by interactions that occur within the same trophic level, such as interspecific competition (Cornelissen et al, ; Fagundes & Fernandes, ; Fagundes et al, ). Studies have reported that the results of interspecific interactions involving phytophagous insects can be habitat‐dependent (Kuchenbecker & Fagundes, ).…”
Section: Introductionmentioning
confidence: 99%
“…Our study shows a strong positive correlation between arthropod herbivore guild diversity and arthropod herbivory rates for N. obliqua. We found no studies analyzing the relation between herbivore guild diversity and herbivore rates, but there are some examples of positive relations between herbivore diversity and abundance (Neves et al, 2010(Neves et al, , 2014Kuchenbecker & Fagundes, 2018). Guild diversity could enhance herbivore abundance (Lewinsohn et al, 2005) potentially explaining greater leaf consumption rates (Siemann et al, 1996;Novotny et al, 2010Novotny et al, , 2012Pinheiro et al, 2016;Muiruri et al, 2019), because of niche complementarity (Gable et al, 2012;Valencia-Cuevas and Tovar-Sánchez, 2015).…”
Section: Discussionmentioning
confidence: 84%